Shuangshen Ningxin capsule alleviates myocardial ischemia-reperfusion injury in miniature pigs by modulating mitophagy: network pharmacology and experiments in vivo - Feifan Jia; Yuanyuan Chen; Gaojie Xin; Lingmei Li; Zixin Liu; Sujuan Xu; Jiaming Gao; Hongxu Meng; Yue Shi; Yanlei Ma; Lei Li; Jianhua Fu (BMC, 2023)
Abstract Background Myocardial ischemia/reperfusion injury (MI/RI) is involved in a variety of pathological states for which there is no effective treatment exists. Shuangshen Ningxin (SSNX) capsule which is developed by Xiyuan Hospital, Chinese Academy of Traditional Chinese Medicine has been demonstrated to alleviate MI/RI, but its mechanism remains to be further elucidated. Methods The MI/RI miniature pigs model was constructed to assess the pharmacodynamics of SSNX by blocking the proximal blood flow of the left anterior descending branch of the cardiac coronary artery through an interventional balloon. The principal chemical compounds and potential targets of SSNX were screened by HPLC-MS and SwissTargetPrediction. The targets of MI/RI were identified based on Online Mendelian Inheritance in Man (OMIM) and GeneCards. Cytoscape 3.9.0 was applied to construct a protein-protein interaction (PPI) network, and Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed using metascape. To further validate the mechanism of SSNX, Molecular docking, Transmission electron microscopy, and Western blot analysis were used to test the effectiveness of targets in related pathways. Results Our results indicated that SSNX significantly improved cardiac function, attenuated myocardial I/R injury. Through network analysis, a total of 15 active components and 201 targets were obtained from SSNX, 75 of which are potential targets for the treatment of MI/RI. KEGG and MCODE analysis showed that SSNX is involved in the mitophagy signaling pathway, and ginsenoside Rg1, ginsenoside Rb1 and ginsenoside Rb2 are key components associated with the mitophagy. Further experimental results proved that SSNX protected mitochondrial structure and function, and significantly reduced the expression of mitophagy-related proteins PTEN-induced putative kinase 1 (PINK1), Parkin, FUN14 domain containing 1 (FUNDC1) and Bcl-2/E1B-19 kDa interacting protein 3 (BNIP3) in MI/RI miniature pigs. Conclusion In our study, the integration of network pharmacology and experiments in vivo demonstrated that SSNX interfered with MI/RI by inhibiting mitophagy.